PENGHIJAUAN BATARAN SUNGAI BILAH DI DESA TEBING LINGGA HARA KECAMATAN BILAH HULU KABUPATEN LABUHANBATU - Fitra Syawal Harahap, Abdul Rauf, Sarifuddin, Abu Yazid (PT.JNDI, JURNAL BIMA, 2023)
Environmental greening is an effort to restore and improve the effectiveness of land so that it can function optimally well.environmental greening is an effort to deal with problems that arise in an area.in this environmental greening activity by utilizing land around the watershed Community service activity bar in the form of